Effect of row pattern and weed-control method on yield and economics of rainfed groundnut (Arachis hypogaea) - DAYAL, DEVI; NAlK, P R; DONGRE, B N; REDDY, P S (The Indian Journal of Agricultural Sciences, 2013)
Â A field experiment was conducted during the rainy seasons (kharif) of 1988 and 1989 at Junagadh to assess the effect of 3 row patterns and 6 weed-control methods on weed growth, yield and economics of rainfed groundnut (Arachis hypogaea L.). Paired row pattern significantly reduced the weed growth at 60 days after sowing and at maturity of groundnut compared With normal row spacing. Paired row of 30-60-30 cm (spacing within pair30 cm, and between pairs 60 cm) x 10cm showed significantly higher weed-control efficiency (55.69%) than normal row pattern (48.34%). Pooled data of row pattern indicated that recommended weed-control method (pre-emergence application of fluchloralin @ 1.50 kg/ha + 1 hand-weeding at 30days after sowing) showed weed-control efficiency equal to that of weed-free treatment. The maximum pod yield (2 254kg/ha) and net return (Rs 7 105/ha) with a benefit: cost ratio of 3.30 were recorded by paired row of 30-60-30 cm x 10 cm. Irrespective of the row pattern, reduction in the quantity of herbicide significantly reduced the weed-control efficiency, pod yield and net return compared with the reconunended weed-control method.